2021
DOI: 10.1155/2021/8863053
|View full text |Cite
|
Sign up to set email alerts
|

Simple Parameters from Complete Blood Count Predict In-Hospital Mortality in COVID-19

Abstract: Introduction. The clinical course of Coronavirus Disease 2019 (COVID-19) is highly heterogenous, ranging from asymptomatic to fatal forms. The identification of clinical and laboratory predictors of poor prognosis may assist clinicians in monitoring strategies and therapeutic decisions. Materials and Methods. In this study, we retrospectively assessed the prognostic value of a simple tool, the complete blood count, on a cohort of 664 patients ( F … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 44 publications
3
21
0
Order By: Relevance
“…In our study, when patient groups by the severity of disease were compared, among all laboratory parameters, only the increase in LI (neutrophils/(monocytes + lymphocytes)) was found to be significant in patients with moderate-to-severe/severe COVID-19. This, in principle, is consistent with the results of a large study, which reported that an increase in the neutrophil/lymphocyte ratio is a prognostically unfavorable marker for COVID-19 outcome [ 3 ]. The underlying mechanisms is not yet clear, but it is considered that inappropriate neutrophil extracellular trap (NET) production plays a key role [ 62 ].…”
Section: Discussionsupporting
confidence: 92%
“…In our study, when patient groups by the severity of disease were compared, among all laboratory parameters, only the increase in LI (neutrophils/(monocytes + lymphocytes)) was found to be significant in patients with moderate-to-severe/severe COVID-19. This, in principle, is consistent with the results of a large study, which reported that an increase in the neutrophil/lymphocyte ratio is a prognostically unfavorable marker for COVID-19 outcome [ 3 ]. The underlying mechanisms is not yet clear, but it is considered that inappropriate neutrophil extracellular trap (NET) production plays a key role [ 62 ].…”
Section: Discussionsupporting
confidence: 92%
“…As observed in many other studies, also for our study population, other baseline laboratory findings routinely assessed exist that contribute to a more accurate prognosis evaluation, such as RDW-CV, D-dimer levels, platelet count, and neutrophil to lymphocyte ratio at the time of hospital admission. RDW-CV is known to be a prognostic biomarker in several diseases [ 50 52 ] and also in COVID-19 patients [ 19 , 53 55 ]; however, at ROC analysis, we obtained a very low sensitivity (RDW-CV values higher than 14.3% displayed 29.3% sensitivity and 89.4% specificity), therefore limiting its usefulness in clinical practice. Increased D-dimer levels and decreased platelet count were initially linked to the onset of disseminated intravascular coagulation (DIC), but today, thanks to the endlessly increase in scientific knowledge about COVID-19 disease, it is gaining attention the hypothesis of a coagulopathy with specific features different from the classical sepsis-related diffuse intravascular coagulopathy [ 56 58 ].…”
Section: Discussionmentioning
confidence: 76%
“…Higher neutrophil count is generally a nonspecific marker of severity, as it is related to both thromboembolic complications and systemic inflammatory responses [ 21 ], while lymphopenia is associated with a dysregulation of immune response [ 14 ]. The neutrophil to lymphocyte ratio thus magnifies the prognostic role of both events, with the ability to predict disease severity [ 19 , 61 , 62 ]. We confirmed a role for this biomarker since a low neutrophil to lymphocyte ratio (ROC curve-based cut − off = 11.78 × 10 3 ) was associated with a shorter hospital stay.…”
Section: Discussionmentioning
confidence: 99%
“…In the study by Corradini et al, WBC was positively associated, and lymphocyte count was negatively associated with the risk of death [ 25 ]. In the study by Bellan et al, the number of WBCs and neutrophils in deceased patients was significantly higher than those discharged, while the number of lymphocytes in deceased patients was significantly lower [ 26 ]. The results of these studies are consistent with the present study.…”
Section: Discussionmentioning
confidence: 99%